Measurements of the associated production of a Higgs boson decaying into two beauty quarks with a weak vector boson - Ambroz, L (2020)
For more than four decades, the Higgs boson has been the most sought-after particle in Particle Physics. Its observation, by the ATLAS and CMS collaborations in 2012, has confirmed the existence of the Higgs field, which is responsible for the spontaneous symmetry breaking mechanism in the electroweak sector and the mass generation of fermions through the Yukawa interaction. Since then, many measurements have been performed, with increasing accuracy, to check whether its properties matched the Standard Model predictions.